POTENSI TANAMAN YANG MEMILIKI AKTIVITAS TERHADAP PROPIONIBACTERIUM ACNES : Systematic Riview: POTENSI TANAMAN YANG MEMILIKI AKTIVITAS TERHADAP PROPIONIBACTERIUM ACNES : Systematic Riview - Muharam, Firman; Rahman Nugraha, Yogi; Mamay, Mamay; Azzahra, Nazwa Aleefha; Sabila, Muthia Nafisa Nur; Fadilah, Astrid Julian; Ramadani, Alya Suci; Aulia Rahma, Devi; Rustamsyah, Ardi (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: Acne (acne vulgaris) is an inflammatory skin disorder commonly experienced by adolescents and adults, with Propionibacterium acnes being the primary bacterium responsible for the inflammation. Increasing antibiotic resistance and the side effects of synthetic drugs have encouraged the use of herbal plants as a safer antibacterial alternative. Objective: This review aims to identify herbal plants that have antibacterial activity against P. acnes, as well as to evaluate the extraction methods, test methods, and inhibition zone effectiveness reported in studies from 2020–2025. Methods: The article was developed through a literature review using Google Scholar with the keywords “activity test,” “plant,” and “P. acnes.” The data analyzed included plant type, extraction technique, testing method, and antibacterial activity results. Results: Maceration with ethanol is the most common extraction method, while antibacterial tests often use disc diffusion and well diffusion. Plants such as bay leaves (Syzygium polyanthum), starfruit leaves (Averrhoa bilimbi), red betel leaves (Piper crocatum), and a combination of pineapple leaves and green betel leaves showed strong inhibition zones (20–24 mm). Guava leaves also provided high activity, while jasmine flowers and porang frog showed weak activity. Conclusion: This study shows that several herbal plants, such as bay leaves, starfruit leaves, and red betel leaves, have strong antibacterial activity against Propionibacterium acnes, while others showed less effectiveness. These results confirm that certain herbal plants have the potential to be developed as natural antibacterials for acne treatment, although further research is needed to determine their mechanism of action, safety, and optimal formulation.